An Industrial systems design study on ELM Movers - Cinco, Ronald Allan M.; Ilagan, Gazel Antonette T.; Mendoza, Lloren S.; Samson, Kristine C. (College of Engineering, 2002)
ELM Movers began its operations on January 1998 with the sole purpose of delivering goods and services for a distribution company. The owner put into use his experience in pharmaceutical distribution into this business. At present ELM Movers offers its' services to Macondray Distribution Company Incorporated which is situated at Libis, Quezon City. It currently employs 17 employees with the owner, Eduardo L. Monzon, being the president. Currently, ELM delivers products of Adams, Pfizer, Van Melle, Chupa Chups and Cadbury. They have 8 vehicles to efficiently deliver the products. Drivers and helpers are paid on a per trip basis. According to the owner, he is satisfied at the rate the business is going. As far as they are concerned, all they have to do is maintain the healthy relationship they have with Macondray and everything will turn out fine. Performance measures may be satisfactory, but the group found out that there is still room for improvement. It is the group's belief that in order for the company to sustain its operation, it must not only rely on one customer, Macondray, but also must find some other sources of income. This claim was based on the overall total market demand on the transport and hauling services particularly on the wholesale and retail of processed food wherein ELM has a small market share. There is still a big market gap to be captured and the group suggested alternatives to market their company through advertising. The group also evaluated the company's strengths, weaknesses and overall potential. The group utilized the idea of benchmarking, which the company can use to measure their performance against similar businesses and find out what can still b done in order to reach a higher level in the industry. Stream analysis was also used to find internal problems that affect productivity of the employees. Environmental factors were also put into consideration. As a result, the group also suggested a preventive maintenance guide to ensure optimum working performance of vehicles and to minimize environmental burdens. All of these alternatives were evaluated according to their costs and benefits.